CARBON ISOTOPE COMPOSITION OF SEDIMENTARY ROCKS IN THE SOUTHERN SIBERIAN PLATFORM AND SURROUNDING FOLD SYSTEMS - Razvozzhaeva E.A.; Nemerov V.K.; Makrygina V.A. (My University, 2007)
Organic carbon isotope composition was studied in the sedimentary cover of the southern Siberian Platform and its surrounding fold systems. The rocks experienced catagenesis, metamorphism, and metasomatism. The chloroform bitumoid (CB) has a stable carbon isotope composition within a wide range of postsedimentation transformations. The average values of δ13C in CB of the sedimentary cover are -29.5‰. Metamorphism and, especially, ore metasomatism, at the Sukhoi Log deposit caused a 2‰ increase in the heavy carbon isotope concentration of CB as compared to that of the platform deposits. The narrow variations in carbon isotope composition of the bitumoid are defined by their derivation from lipids, whose components are almost insusceptible to changes in the PT conditions. Kerogen from platform deposits is more strongly depleted than CB in the heavy carbon isotope (δ13Cav-32.2‰). The insoluble carbonaceous matter (ICM) of the metamorphic shales is significantly enriched in the heavy carbon isotope (δ13 Cav-21.9‰). The highest changes in carbon isotope composition were found in concentrates of ICM from metasomatically altered rocks of the Sukhoi Log deposit (δ13 Cav-17.5‰). The heavier carbon isotope composition caused by metamorphism and metasomatism is evidently defined by isotopic exchange between the carbonate carbon and CO2 of metasomatic solutions, on one hand, and ICM of shales, on the other. © Pleiades Publishing, Ltd. 2007.